Performance Measurement of Human Resources PT. Pulau Bintan Jaya Based on the Human Resource Scorecard Model - Mardiyah, Mardiyah; Lumbanraja, Prihatin; Madya, Faizal (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2021)
PT Pulau Bintan Jaya is one of the foreign investment companies producing crumb rubber in Riau Islands Province. The company had been in operation since 1969, producing rubber with a few measures which were Standard Indonesian Rubber (SIR) 5, SIR 10, and SIR 20 per customer request. Companies have conducted employee performance measurements but have not specifically measured employee performance by linking it to company strategic functions. Current performance assessments are not yet focused on human resource development efforts. There were still poorly educated employees who served as team leaders and as supervisors. As a result, work-related communication became difficult and led to multiple obstacles under which employment resources became inadequate, and the targets of corporate performance unattainable. There are issues relating to the quality of human resources, and companies have been declining demand and declining production rates for several months. The decline in demand from customers has become one of the issues to evaluate in the company's performance measurement, due to its inadequate strategic resource management. It requires alightnment of the work systems to capture the role of human resources, while in this regard some current case work accident are still faund annually in the production section, even though for the past three consecutive years the accident rate has declined, it needs to be figured out by performing performance measurements. A human resource scorecard measures the performance of human resources by finding solutions to the weaknesses of human managerial resources in PT. Pulau Bintan Jaya, and assist in linking mission vision and strategic objectives. In this study, the design results were obtained as follows: there are 15 strategic goals and 32 Key Performance Indicators, special elements of the human resource system can be driven by 16 performance drivers (called Lagging Indicators), and 16 performance outputs to be achieved (called Leading Indicators), while the results Measurement of employee performance in PT Pulau Bintan Jaya using the Human Resource Scorecard method obtained good results.